The Concept of Love in Nizar Qabbani's Qamus Al-Ashiqin: A Semiotic Study According to Roland Barthes - Faiz, Muhammad; Handayani, Rizqi; Kamil, Sukron; Ridha, Hanifah (Jurusan Bahasa dan Sastra Arab Universitas Islam Negeri Alauddin Makassar, 2025)
This study investigates the representation of love in Nizar Qabbani's poetic anthology “Qamus al-Ashiqin” through Roland Barthes' semiotic theory, with an emphasis on its mythical layer in the context of Arab culture. The research explores the use of signs and symbols that denote, connote, and mythologize love in Qabbani's poetry. Using a qualitative descriptive method and textual analysis, this study focuses on the poem titled “Qamus al-Ashiqin”. The data were collected through documentation, quoting, and close reading. Findings show that Qabbani presents love not only as a personal emotion but also as a cultural ideology, often embodying sacrifice, longing, and transcendence. The mythical meanings embedded in the poems reflect broader Arab cultural values concerning love. This research contributes to Arabic literary studies by contextualizing semiotic analysis in Arabic poetry and offers a fresh perspective on Barthes' theory within a non-Western literary tradition.